Efforts To Improve Agility And Speed In Playing Football At Sdn 44 Lubuk Anau - Elmedi Elmedi (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. Problems to be studied in this research are: a. How to improve learning outcomes penjaskes especially soccer game using cooperative learning methods on students SDN 44 Lubuk Anau? b. The steps taken to improve the outcome of the guidance in January 2016? This research is a research action (action research) Because research done to solve the problem of learning in class. This research also includes descriptive research, because it describes how a learning technique is applied and how desired results can be achieved. According to Oja and Sumarjan (in point sugiarti, 1997: 8) there are four different types of action research, namely: (1) teacher action research as a researcher, (2) collaborative action research, (3) research of interlinked simulative action. (4) experimental social action research. In this action research uses collaborative research forms with teacher training eyes and in the teaching and learning process in the classroom as a teacher is the teacher of training eye while peneiti acts as an observer, the full responsibility of action research is observer (researcher). Data Analysis Technique, To know the effectiveness of a method in learning activities need to be held data analysis. In this research using qualitative descriptive analysis technique, that is a research method that is describe reality or facts in accordance with the data obtained with the aim to know learning achievements achieved sisw also to obtain student responses to learning activities and student activities during the learning process To analyze the success rate or percentage of students' success after the learning process each round is done by giving evaluation in the form of practice test at the end of each round. This analysis is calculated by using simple statistic that is: For learning mastery, There are two categories of mastery learning that is individual and classical. Based on the guidance of the implementation of teaching and learning curriculum 1994 (Depdikbud, 1994) that students have complete learning when the class gets 85% who have reached the absorption. From the results of learning activities that have been done for three cycles and based on the entire pembahaan and analysis that has been done can be concluded as follows: Learning by the method of learning play methods have a positive impact in improving student learning achievement characterized by the improvement of student learning completeness in each cycle, cycle I (61,54%), cycle II (89,74%), while for affective aspect that is cycle I (84,62%), cycle II (100%) Application of learning method of play method have positive influence, that can increase student learning motivation which is indicated by the average of students' answers which states that students are interested and interested in learning method of play method so that they are motivated to learn.